1979
DOI: 10.1007/bf01252706
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic activity and transcendental meditation

Abstract: Ten male advanced meditators and ten male long-term meditators subjected themselves four times to slight physical exercise following a period of rest, meditation or reading. Daily urine excretions of catecholamines and VMA were determined in both groups. On the experimental days 4-hour urine specimens, one before and one after the experiments, were again collected for analysis. During the experiments blood pressure and heart rate were measured continuously and blood samples were taken for plasma catecholamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 22 publications
1
17
1
Order By: Relevance
“…The studies showed reduced somatic arousal with some physiological changes suggestive of increased alertness. The findings of increased alertness was supported by a study by Lang et al 6 In this study meditators who had 2 to 3 years of experience practicing TM had lower 24-hour urinary catecholamines compared to meditators with an average experience of 4.1 years. The findings contradict the idea that meditation is simply a state of reduced sympathetic activity but supports the idea of it being a ''calm yet alert'' state.…”
supporting
confidence: 76%
“…The studies showed reduced somatic arousal with some physiological changes suggestive of increased alertness. The findings of increased alertness was supported by a study by Lang et al 6 In this study meditators who had 2 to 3 years of experience practicing TM had lower 24-hour urinary catecholamines compared to meditators with an average experience of 4.1 years. The findings contradict the idea that meditation is simply a state of reduced sympathetic activity but supports the idea of it being a ''calm yet alert'' state.…”
supporting
confidence: 76%
“…Meditation practices are reported to enhance the melatonin levels (Tooley et al, 2000), the precursors of melatonin especially the serotonin (Bujatti and Riederer, 1976) and noradrenalin (Lang et al, 1979). Meditation increases melatonin concentration by slowing its hepatic metabolism or augmenting the synthesis in the pineal gland (Massion et al, 1995).…”
Section: Meditation Melatonin and Sleepmentioning
confidence: 99%
“…However, a different effect of TM practice was suggested by another early study which reported changes in plasma noradrenaline after TM in long-term meditators (with 2–3 years experience of TM) and advanced meditators (with 4.1 years average experience of TM) [7]. Advanced meditators had higher 24-h urinary catecholamines compared to long term meditators.…”
Section: Introductionmentioning
confidence: 98%